A visible-light-responsive metal–organic framework for highly efficient and selective photocatalytic oxidation of amines and reduction of nitroaromatics. Issue 47 (22nd November 2019) - Chen, Peiqi; Guo, Zhifen; Liu, Xin; Lv, Hui; Che, Yan; Bai, Rong; Chi, Yanhong; Xing, Hongzhu
Abstract : A novel visible-light-responsive metal–organic framework for highly efficient and selective transformation of amines and nitroaromatics to produce imines and anilines. Abstract : Photocatalysis is a green synthetic method for organics transformation. We present here the synthesis of a novel visible-light-responsive metal–organic framework and its photocatalytic application. The prepared MOF is highly efficient for the self-coupling of primary amines and oxidative dehydrogenation of secondary amines to selectively produce imines assisted by the green and economic oxidant of molecular oxygen. Studies reveal that both energy transfer and electron transfer from the photoexcited MOF to molecular oxygen are important for amine oxidation, where the highly reactive species of superoxide radicals and singlet oxygen together account for the high catalytic performance. The photogenerated electrons of the MOF have also been utilized for the reduction of aromatic nitroarenes. Results show that they are highly selective for the reduction of nitroarenes to produce anilines in the presence of hydrazine hydrate. The work demonstrates the enormous potential of photoactive MOFs for converting organic substrates into valuable chemicals.